Outcomes of in‐hospital cardiopulmonary resuscitation for patients with end‐stage liver disease. (26th March 2019) - Ufere, Nneka N.; Brahmania, Mayur; Sey, Michael; Teriaky, Anouar; El‐Jawahri, Areej; Walley, Keith R.; Celi, Leo A.; Chung, Raymond T.; Rush, Barret
Abstract: Background and Aims: There have been improving survival trends after in‐hospital cardiac arrest for the general population, but there is limited information on the outcomes of hospitalized patients with end‐stage liver disease (ESLD) who undergo cardiopulmonary resuscitation (CPR). We aimed to examine survival to hospital discharge after receipt of in‐hospital CPR in patients with ESLD using a nationally representative sample. Methods: We used the Nationwide Inpatient Sample database from 2006 to 2014 to identify adult patients who underwent in‐hospital CPR. Using multivariate modelling, we compared survival to hospital discharge for patients with ESLD to those without ESLD. We also compared outcomes of patients with ESLD to patients with metastatic cancer. Results: A total of 177 533 patients underwent in‐hospital CPR, of which 1474 (0.8%) had ESLD. Patients with ESLD had lower rates of survival to hospital discharge compared to patients without ESLD (10.7% vs 28.6%, P  < 0.01). In multivariate modelling, ESLD was significantly associated with lower odds of survival to hospital discharge after in‐hospital CPR (OR 0.35, 95% CI 0.28‐0.44, P  < 0.01). Among survivors of in‐hospital CPR, ESLD patients had a significantly lower chance of discharge to home compared to patients without ESLD (3.2% vs 8.0%, P  < 0.05). Patients with ESLD also had lower rates of survival to hospital discharge compared to those with metastatic cancer (10.7% vs 15.5%, P  < 0.01). Conclusions: Outcomes are poor after in‐hospital CPR in patients with ESLD and are worse than for patients with metastatic cancer. The current analysis can be used to inform goals of care discussions for patients with ESLD.